Multi‐Year Estimates of Daily Heat Transport by the Atlantic Meridional Overturning Circulation at 34.5°S. Issue 5 (25th April 2021) - Kersalé, M.; Meinen, C. S.; Perez, R. C.; Piola, A. R.; Speich, S.; Campos, E. J. D.; Garzoli, S. L.; Ansorge, I.; Volkov, D. L.; Le Hénaff, M.; Dong, S.; Lamont, T.; et al.
Abstract: Variations in the mass and heat transported by the meridional overturning circulation (MOC) have important, well‐documented, influences on global and regional climate, weather, ecosystems, and coastal sea levels. However, continuous, high‐frequency, observations of these quantities have been limited to date. Multiple years of full‐depth daily observations from moored instruments in the South Atlantic at 34.5°S are combined with satellite observations to resolve the volume transports in both the upper and abyssal MOC cells, and the associated full‐depth meridional heat transport (MHT), on daily to interannual timescales. A newly developed method for combining satellite sea level observations with historical hydrographic measurements was used to estimate daily full‐depth ocean profiles of temperature in the ocean interior where mooring coverage is sparse. The average MHT during 2013–2017 is 0.5 PW, with a daily standard deviation of 0.8 PW. The MHT variability is most strongly driven by the geostrophic relative velocity contributions (horizontal density‐gradient changes). This variability is highly correlated with the volume transport variability of the MOC upper cell ( r = 0.96) and modestly anti‐correlated ( r = −0.52) with the abyssal cell variations. An empirical relationship between the MHT and MOC values was developed allowing the reconstruction of a longer MHT time series including the pilot array period (2009–2010). Seasonal variation of the MHT is significant, and results from strong variations of all terms (Ekman, barotropic, and baroclinic). Although the 2013–2017 shows an increasing MHT trend (0.14 PW/year), the longer time period record suggests that the apparent trend may simply be interannual modulation of MHT at 34.5°S. Plain Language Summary: Changes in the meridional overturning circulation, a large system of ocean currents driven by differences in temperature and salt content as well as the winds, are known to have significant influences on the global climate system. This study presents, for the first time, full‐depth, daily measurements of the volume and heat transported by this circulation system in the South Atlantic at 34.5°S based on direct observations. As the instruments anchored on the seafloor are too widely spaced in the basin interior, a new method for using satellite observations to estimate interior temperature profiles was developed and used. The roughly 4 years of continuous daily data reveal seasonal and interannual changes of these important flows. The observations also demonstrate that the volume and heat transports vary in a consistent manner with one another. This allows us to use some earlier moored observations from a pilot version of the array, extending the data record further back in time and producing ∼6 years of daily estimates of heat transport in the South Atlantic during 2009–2017, with a gap during 2010–2013. Key Points: Implementation of a novel methodology for computing the daily meridional heat transport time series at 34.5°S from 2013 to 2017 The heat transport has significant variability highly correlated with changes in the strength of the meridional overturning circulation A reconstructed/extended meridional heat transport time series allows analysis of seasonal to interannual changes and long‐term trend